Broadened T-cell Repertoire Diversity in ivIg-treated SLE Patients is Also Related to the Individual Status of Regulatory T-cells - Costa, Nuno (2016)
Intravenous IgG (ivIg) is a therapeutic alternative for lupus erythematosus, the mechanism of which remains to be fully understood. Here we investigated whether ivIg affects two established sub-phenotypes of SLE, namely relative oligoclonality of circulating T-cells and reduced activity of CD4 + Foxp3+ regulatory T-cells (Tregs) reflected by lower CD25 surface density.